2014
DOI: 10.11648/j.sr.20140205.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sexual Violence and Associated Factors among High School Students in Harari Regional State, Harar Town, Eastern Ethiopia

Abstract: Abstract:Background: Sexual violence is any sexual act that is perpetrated against someone's willingness including a completed and or attempt nonconsensual, abusive sex act. This study aimed to determine sexual violence and associated factors among high school students in Harar town, Eastern Ethiopia. Methods: Institutional based cross-sectional study was conducted among youth in high school students. Self administered questionnaire was used to collect quantitative data from randomly selected 432 students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
5
7
2
Order By: Relevance
“…When I compared with other past study on sexual violence, a study conducted in Harare revealed that students used addictive drugs like alcohol (18%), chat and shish (7.2%) as very important contributing factors for sexual violence's [12,7]. Also this study finding supports my study findings.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…When I compared with other past study on sexual violence, a study conducted in Harare revealed that students used addictive drugs like alcohol (18%), chat and shish (7.2%) as very important contributing factors for sexual violence's [12,7]. Also this study finding supports my study findings.…”
Section: Discussionsupporting
confidence: 80%
“…Other study conducted in Harare indicates that females dressing style, their act, peer pressure, revenge and males emotionality identified as contributing factors for sexual violence [12,7].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Gender difference was not considered as an important issue in exposing children to violence by 58% of the respondents and gender difference is not signi cant predictor at the nal regression model too. This nding is in line with what had been reported from else where (21) .…”
Section: Discussionsupporting
confidence: 93%